Alterações ultrassonográficas de paratireóide podem predizer evolução clínica de pacientes em diálise com hiperparatirioidismo secundário? - Claudia Ribeiro (2009)
Introduction: The ultrasonographic finding of increased parathyroid indicates poor response to treatment in patients with hyperparathyroidism secondary to renal insufficiency (RI).Methods: Eighty-five patients with levels of PTH higher than800pg/mL, from January 2005 to January 2006 were submitted to US and followed until January 2009. We evaluated laboratory parameters, clinical and demographic data and occurrence of death, vascular events and bone disease. Results: Fifty-three patients (62.4%) had parathyroid nodules and higher levels of PTH, Ca and P. There was no association between nodule occurrence AND morbidity or mortality. Patients who underwent parathyroidectomy (n = 15) showed significant improvement in phosphorus levels as well as Ca x P product (P = 0.03 and 0.006 respectively). They also had lower mortality (32% vs 68%, p = 0.01) and lower incidence of cardiovascular or cerebrovascular events (27% vs 73%., P = 0.02). Calcium x Phosphorus product above 55mg ² / dL (RR 1.48 [1.06, 2.08], p = 0.03), presence of vascular calcification (1.33 [1.01, 1.76], p = 0.015) previous occurrence of vascular events (RR 2.25 [1.27, 3.98], p <0.001) were risk factors for mortality in this population.Conclusion: The presence of parathyroid nodules in ultrasound (US) is associated with worse metabolic profile in patients with severe hyperparathyroidism, but cannot predict clinical outcome of these patients. Parathyroidectomy is associated with lower cardiovascular morbidity and mortality in patients with nodules. Further studies areneeded to define the usefulness of US in the evaluation of hyperparathyroidism secondary to IR.